Mapping the online audiovisual memory of the Journalism courses from the Reuni Program in Brazil - Souza, José Jullian Gomes de (Informação em Pauta, 2020)
This article aims to investigate the process of storing audiovisual memory on online platforms, based on the Journalism courses created by the Program to Support Federal University Restructuring and Expansion Plans (Reuni). The general objective is to investigate whether and how the (15) fifteen new Journalism courses created by Reuni are archiving and making these documents available on the online platform. And the specifics objectives: a) to map the new Journalism courses created by Reuni and the disciplines linked to telejournalism / audiovisual and b) to talk about the new places of memory, as a contribution to the online filing. As a methodological contribution, it starts with the quantitative-qualitative approach and exploratory-descriptive research strategy, whose aim is to identify the absence or presence of audiovisual collections online in these selected courses. The considerations on this mapping point to the visualization of few digital preservation practices and the need to create guidelines and institutional policies to intensify this practice or for it to be adhered to by these institutions.